SOLITARY PULMONARY NODULES: EFFECTIVENESS OF DYNAMIC CT IN THE DIFFERENTIAL DIAGNOSIS - N. K. Silanteva; A. P. Petrosian; Z. N. Shavladze; A. Yu. Usacheva; Yu. A. Ragulin; V. S. Usache (Сибирский онкологический журнал, 2017)
The differential diagnosis of solitary pulmonary nodules remains a challenge in oncology. Dynamic contrastenhanced CT is a potentially valuable tool capable of detecting malignancy. The purpose of the study was to evaluate the value of dynamic CT in the differential diagnosis of solitary pulmonary nodules. Material and methods. Fifty two patients with solitary pulmonary nodules underwent CT examination using a GE Optima CT660. The CT protocol included: 1) scan volume from the jugular notch to the end of the diaphragmatic dome; 2) location of the nodule in the lung; 3) scanning time for 30 sec, 1 min, 2 min, 4 min and 6 min following contrast agent injection. The image processing was carried out on an Advantage Workstation for Windows (AW4.5, GE Healthcare). The CT findings were verified by histology after CT-guided transthoracic biopsy of lung lesions and lung surgeries. Results. The sensitivity, specificity and accuracy of dynamic contract-enhanced CT were higher than those without dynamic CT (85, 95 and 92 % versus 71, 95 and 88 %, respectively).